Secretory Breast Carcinoma: A Histopathologic and Genomic Spectrum Characterized by a Joint Specific ETV6-NTRK3 Gene Fusion. (November 2015) - Del Castillo, Marie; Chibon, Frédéric; Arnould, Laurent; Croce, Sabrina; Ribeiro, Agnès; Perot, Gaëlle; Hostein, Isabelle; Geha, Sameh; Bozon, Catherine; Garnier, Agnès; Lae, Marick; Vincent-Salomon, Anne; et al.
Abstract : Secretory breast carcinoma (SBC) is a rare breast carcinoma with distinctive morphologic features and a recurrent specific chromosomal translocation t(12;15)(p13;q25), usually of low histologic grade and favorable prognosis. We describe the morphologic and genetic characteristics of 11 cases of SBC from 10 patients. Histologic and immunohistochemical analyses, fluorescence in situ hybridization using break-apart probes specific to ETV6 on 12p13, reverse transcription polymerase chain reaction with in-house probes specific to the ETV6-NTRK3 gene fusion, and DNA copy number variation by array comparative genomic hybridization analyses were performed on all cases. Seven cases were of low histologic grade, 3 were intermediate, and 1 had high-grade nuclear atypia, necrosis, and numerous mitoses. This patient had a fatal outcome. Five cases displayed low hormonal receptor expression, whereas the rest had basal-type immunoprofiles. All interpretable cases harbored an ETV6-NTRK3 gene fusion by reverse transcription polymerase chain reaction and/or an ETV6 rearrangement by fluorescence in situ hybridization, with duplication of the oncogenic derivative in 2 cases. Array comparative genomic hybridization analysis showed simplex genomic profiles. The 2 cases with ETV6-NTRK3 duplication included a gain of 12p starting from the ETV6 locus to the telomere, associated with a gain of the 15q from the centromere to NTRK3 in 1 case, and in the other a normal profile up to NTRK3 on 15q, and then a loss up to the telomere, suggesting loss of corresponding normal chromosome 15. These findings provide a novel insight into the morphologic and genetic spectrum of SBC, ranging from low-grade to high-grade histology, with occasional low hormonal receptor expression, simplex genomic profiles, and possible unfavorable course.